2017
DOI: 10.3310/hta21420
|View full text |Cite
|
Sign up to set email alerts
|

Managing Faecal INcontinence in people with advanced dementia resident in Care Homes (FINCH) study: a realist synthesis of the evidence

Abstract: BackgroundEighty per cent of care home residents in the UK are living with dementia. The prevalence of faecal incontinence (FI) in care homes is estimated to range from 30% to 50%. There is limited evidence of what is effective in the reduction and management of FI in care homes.ObjectiveTo provide a theory-driven explanation of the effectiveness of programmes that aim to improve FI in people with advanced dementia in care homes.DesignA realist synthesis. This was an iterative approach that involved scoping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 201 publications
(243 reference statements)
0
21
0
Order By: Relevance
“…After title and abstract screening, and removal of duplicates, 55 articles were reviewed at full-text level. From these, 18 articles [21,23,30,32,33,[68][69][70][71][72][73][74][75][76][77][78][79][80] (see Fig. 1 for the PRISMA flow chart) were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After title and abstract screening, and removal of duplicates, 55 articles were reviewed at full-text level. From these, 18 articles [21,23,30,32,33,[68][69][70][71][72][73][74][75][76][77][78][79][80] (see Fig. 1 for the PRISMA flow chart) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Among the eligible articles were three studies that were reported in two or more papers. Specifically, the 'FINCH' study was reported in three papers [69,70,77]. Similarly, Ostaszkiewicz reported on different aspects of the same Grounded theory study about providing continence care in Australian residential aged care homes (RACH) in three papers [32,72,73].…”
Section: Resultsmentioning
confidence: 99%
“…A recent review argues that addressing the specific challenges (eg, recognizing the urge to defecate, remembering where the toilet is) that arise when providing continence care to people with dementia is likely to be key to helping to reduce FI in this population. 55 Many people with FI also experience urinary incontinence, hence the term double fecal incontinence. This review found high prevalence of double FI among older people living in care homes.…”
Section: Discussionmentioning
confidence: 99%
“…People with dementia have among the highest levels of multi-morbidiity of any long term disorder (27). As the population ages the prevalence of dementia and incontinence is increasing, as are the number of people living at home with both these conditions (28). Incontinence is common in people with severe dementia and those approaching the end of life and is a powerful predictor of admission to long term care facilities.…”
Section: Multi-morbiditymentioning
confidence: 99%